Термодинамика и кинетика вытеснения водорода из воды многокомпонентными сплавами - Зипунников, Николай Николаевич; Трошенькин, Борис Александрович (НТУ "ХПИ", 2009)
In article the calculated values of constants balance reaction of interactions calcium, strontium, barium and magnesium with water and water steam at reception of hydrogen. Accounting formulas of fullness reactions for reception the hydrogen in depending on constants of the balance. The generalization of the experience date has been provided on the foundation of Gibbs-Folmer equations.
Keywords: давление водорода; оксид кальция; температура плавления